Gen Z’s Intention to Use QRIS in Semarang: The Moderating Role of Financial Literacy - Salsa Filiya; Dwi Eko; Dian Prawitasari; Rudi Kurniawan (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of lifestyle compatibility, hedonic motivation, and perceived ease of use on the intention to use cashless payment systems, with financial literacy as a moderating variable among Generation Z university students in Semarang, Indonesia. A quantitative approach was employed using Structural Equation Modeling (SEM) with SmartPLS 3.0 software and purposive sampling involving 200 respondents. The findings reveal that lifestyle compatibility and perceived ease of use have a positive and significant effect on the intention to use cashless payments, while hedonic motivation shows no significant effect. Furthermore, financial literacy significantly moderates the relationship between lifestyle compatibility and intention to use, but does not moderate the relationship between hedonic motivation or perceived ease of use and behavioral intention. These results suggest that alignment with user lifestyles and ease of use are crucial factors in driving the adoption of cashless payment technologies, particularly when supported by adequate financial literacy.